Morphological Analysis of Prefixes in the Makasae Language - Antonio Constantino Soares (Syntax Corporation Indonesia, 2025)
This study examines the morphological processes in the Makasae language, focusing on the use of prefixes ‘Au’- and ‘Tuli’- to form adjectives and verbs. Makasae, a language spoken primarily in East Timor, belongs to the Trans-New Guinea language family and features a rich system of affixation. The research employs a qualitative descriptive approach to analyze data collected through elicitation tasks and sentence construction with native speakers. The study examines how the prefix ‘Au’- attaches to various root words to create descriptive adjectives, while ‘Tuli’- combines with verb roots to form dynamic and forceful action verbs. The findings highlight the productivity and regularity of these prefixes in shaping Makasae’s verbal and adjectival morphology. ‘Au’- is found to serve as an adjectivizing tool, whereas ‘Tuli’- contributes to the formation of action-oriented verbs with a sense of intensity or aggression. The study contributes to a deeper understanding of Makasae’s affixation system and its role in the broader context of Trans-New Guinea linguistics. Further research is recommended to explore additional morphological processes and regional variations in the use of these affixes.